Recurrent Aphthous Stomatitis Affects Quality of Life. A Case-Control Study - Rivera C; Muñoz-Pastén M; Núñez-Muñoz E; Hernández-Olivos R (Dove Medical Press, 2022)
César Rivera,1 Mariagrazia Muñoz-Pastén,2 Esteban Núñez-Muñoz,2 Romina Hernández-Olivos2 1Department of Basic Biomedical Sciences, Faculty of Health Sciences, Universidad de Talca, Talca, Chile; 2Department of Stomatology, Faculty of Dentistry, Universidad de Talca, Talca, ChileCorrespondence: César Rivera, Department of Basic Biomedical Sciences, Faculty of Health Sciences, University of Talca, Lircay Av. S/N, Office No. 8, Talca, Maule Region, 3460000, Chile, Tel/Fax +56 71 2418855, Email cerivera@utalca.clAim: To determine the impact of recurrent aphthous stomatitis on quality of life related to oral health, and then to determine the relationship between the observed impact and lesions characteristics.Methods: In this prospective case-control study (n=62), patients were divided into a healthy group (people with no history of ulcers) and recurrent aphthous stomatitis (people who had an active ulcer at study entry). The latter were also evaluated when the lesion disappeared (remission stage). We record the quality of life in all groups using the impact profile of oral health in its abbreviated Spanish version (OHIP-14SP). Finally, we correlate the clinical characteristics of the lesions with the levels of quality of life.Results: All the lesions were of the minor morphological type. Most of the lesions were located on the lining mucosa, primarily on the lips. Patients report a lower quality of life during ulcer episodes compared to ulcer-free periods, and this impact is positively related to the number and size of lesions.Conclusion: We concluded that recurrent aphthous stomatitis increased the negative effects of oral health on the quality of life of patients. The number and size of ulcers are responsible for this impact. Our results suggest that, if intervened locally, general relief of the condition could be achieved.Keywords: aphthous ulcers, quality of life, health-related quality of life, case-control studies